The inner world : a psycho-analytic study of childhood and society in India - Kakar, Sudhir (New Delhi : Oxford University Press, 2012)
Feelings, impulses, wishes, and fantasies - the dynamic content of the inner world - occupy the deepest recesses of the psyche. It is through introspection and empathy, essential to psychotherapy, that the outside observer can grasp the meaning of the inner world of an individual.
This ed. originally published: 2008.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Keywords: Personality and culture -- India; Child psychology -- India; Psychoanalysis and culture -- India; Hinduism -- Psychology